Structure of non-economic factors of economic growth and complex development of society - Shavel, Sergei A. (Journal of the Belarusian State University. Sociology, 2019)
The apophatic nature of non-economic factors, their attributive characteristics and practical involvement in economic life are considered. It is revealed through such factors as expectation, trust, archetypes, consensus, etc.